PREACHING GOSPEL TO ALL CREATURES (An Ecological - Theological Description) - Ibelala Gea (Jurnal Teologi Cultivation, 2018)
AbstrakArtikel ini bertujuan untuk mendeskripsikan hasil penelitian tentang bagaimana memberitakan Injil kepada seluruh makhluk, bertolak dari Markus 16:15-16. Pemberitaan Injil adalah menyadarkan manusia agar tidak hanya memandang alam sebagai kekuasaan (dominio) tetapi sebagai sesama ciptaan, sahabat yang bersifat communio. Memberitakan Injil kepada seluruh makhluk dan menghargai segala makhluk dengan saling memberi dan menerima dengan mengacu pada pola-pola reduce, reuse, recycle dan replace sebagai tanggung jawab kepada Tuhan yang telah memberi amanat.Kata Kunci: Injil dan Segala makhlukAbstractThis article aims to describe the results of research on how to preach the gospel to all beings, based on Mark 16:15-16. Preaching the gospel is a great commission from the Lord Jesus to His followers after His resurrection from the dead. The world is the address of the gospel preaching, not only to man but to all beings.The Gospel writer of Mark wants to explain that the world is synonymous with evil, therefore the gospel serves to salt the evil world, so when Iniil is preached to the wicked, it is expected to change the mindset and human behavior.Greedy and greedy human behavior that only views nature as a commodity.Human evil is seen when only the task of exploiting natural resources and forget the responsibility of caring for, nurturing nature and the environment. Gospel preaching aims to awaken peoples not only to view nature as power (dominio) but as a fellow of creatures, and friends(communio).Preach the gospel to all beings and receiving each other with referring to reduce, reuse, recycle andreplace as a responsibility to God who has given the mandate for us.Keywords: gospel and All Creaturess.